MODERATE YOUTH PROGRAM: SHAPING FUTURE GENERATIONS OF LEADERS WHO RESPECT DIVERSITY AND RELIGIOUS TOLERANCE - Muhammad Wandisyah R Hutagalung; Nurintan Muliani Harahap; Siti Wahyuni Siregar (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2026)
This community service program, titled "Moderate Youth Program: Shaping Future Leaders Who Respect Diversity and Religious Tolerance" was implemented in Tapanuli Tengah Regency, North Sumatra, Indonesia. The program addressed the elevated risk of religious conflict in this pluralistic region, where Muslim and Christian populations are nearly equal in proportion (42.53% and 57.32%, respectively). Employing the Participatory Action Research (PAR) method, the program engaged youth from Islamic and Christian organizations, local religious leaders, and the Forum for Religious Harmony (FKUB) as active participants and co-researchers throughout all stages of implementation. The activities included workshops, dialogues, and conflict resolution simulations, which enhanced participants' understanding of religious moderation and provided them with practical skills for mediating conflicts and promoting tolerance. Key outcomes included increased youth awareness of the importance of interfaith dialogue, the establishment of interfaith youth networks, and the formulation of a joint action plan to sustain peacebuilding initiatives. The program demonstrates the strategic role of youth in promoting harmony and social cohesion in a multicultural setting. Future program improvements should include geographic expansion, broader stakeholder inclusion, and integration of digital platforms to support sustained community engagement.